Rule of Law and Good Governance in Nigeria: Challenges and Cures - Atiyaye, Dauda Mohammed; Cheri, Lawan; Kaku, Mohammed; Kele, Ali; Goni, Umar Mohammed (Kashere Journal of Politics and International Relations, 2025)
Despite an advancement in science and humanities, Nigerian still struggle with the issue of development. Rule of law and good governance are the major features of any civilized society today. The rule of law is a liberty centred constitutional concept which stipulates that everything must be done in accordance with the law. The rule of law is fundamental and prerequisite for good governance. Good governance floats on the rule of law, while the good governance promotes and sustains rule of law. Nigeria today, struggles with ensuring that the law applies equally to all. Corruption and bad governance have planted seeds that have stumped the progress of the rule of law and in turn negatively impacted the standard of living and development of Nigeria. The objective of this paper is to find out the extent to which rule of law has influenced good governance in Nigeria. Secondary data, generated through articles, books, scholarly journals were used for the analysis. Our findings indicate that, in principle, rule of law are elaborately provided in Nigeria, but in practice, good governance still eludes the country. Corruption, poverty, ignorance, inflation, declining productivity, maladministration, dictatorship, ethnicity and other primordial factors, as well as prevalent social vices are the road mines to good governance in Nigeria. Equitable distribution of resources, provision of qualitative education, economic restructuring of the society, freedom of the press and political reforms, among other recommendations, are fundamental for the enthronement of functional rule of law for good governance in Nigeria.